2011
DOI: 10.1088/0253-6102/56/3/24
|View full text |Cite
|
Sign up to set email alerts
|

Dark Energy

Abstract: We review the problem of dark energy, including a survey of theoretical models and some aspects of numerical studies.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
568
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 770 publications
(576 citation statements)
references
References 1,089 publications
(1,137 reference statements)
4
568
0
4
Order By: Relevance
“…Nevertheless, these dynamical dark energy models offer the simplest extension of ΛCDM and have been extensively studied (see for example ), and often go under the name quintessence. For reviews and further references, see [85][86][87][88][89][90][91][92].…”
Section: Dynamical Dark Energymentioning
confidence: 99%
“…Nevertheless, these dynamical dark energy models offer the simplest extension of ΛCDM and have been extensively studied (see for example ), and often go under the name quintessence. For reviews and further references, see [85][86][87][88][89][90][91][92].…”
Section: Dynamical Dark Energymentioning
confidence: 99%
“…On the other hand, in recent years, a wealth of dynamical DE models with a time-varying EoS has been proposed (Copeland et al 2006;Li et al 2011;Bamba et al 2012). Observationally, the latest astronomical data from SNe Ia, CMB and BAO experiments show that dynamical DE models with time-varying EoS parameter are mildly favored (Zhao et al 2012;Alam et al 2004;Gong 2005;Gong & Zhang 2005;Huterer & Cooray 2005;Wang & Tegmark 2005).…”
Section: Introductionmentioning
confidence: 99%
“…V, highlighting the testable prediction of a zero tensor-to-scalar ratio in the primordial power spectra. Reviews can be found in [30][31][32] for dark energy and [33][34][35][36][37] for inflation.…”
Section: Introductionmentioning
confidence: 99%